Controlling the Composition, Morphology, Porosity, and Surface Chemistry of Lignin-Based Electrospun Carbon Materials - García-Mateos, Francisco J.; Ruiz-Rosas, Ramiro; Rosas, Juana M.; Rodríguez-Mirasol, José; Cordero, Tomás (Frontiers in Materials, 2019)
Electrospinning is a suitable top-down technique for the preparation of polymeric fibers using high voltage electrical fields and solutions of the selected polymer of adequate viscosity and conductivity. The versatility of electrospinning allows accurate control of the morphology and composition of the fibers by a wide combination of operating conditions and small modifications of the spinneret and collector. Alcell lignin, which is extracted from lignocellulosic biomass using organic solvents through Organosolv process, is readily solved in ethanol, producing a solution that matches the requirements of the electrospinning process. This review summarizes the vast collection of carbon materials that can be obtained by processing lignin using electrohydrodynamic forces. The coaxial and triaxial electrospinning setups allow for obtaining fibers with two or more components hierchically arranged, the use of these configurations along with a carefully setting of the operating conditions (distance between needle and collector, voltage, flow rate,…) and the solution properties (conductivity, viscosity,…) facilitates the conformation of lignin into spheres, beaded fibers, straight fibers and fused meshes. All these morphologies can be implemented with solid or hollow bodies (i.e. enabling the production of tubes and hollow spheres) by using a sacrificial templating agent. Phosphoric acid can also be added in small amounts to the lignin solution, shortening the thermostabilization time of the fibers. The porosity of the phosphorus containing carbon fibers can be modified in the last stage of the preparation of carbon fibers by controlled gasification process, owing to the extended oxidation resistance of the P-doped fibers. Fibrillar carbon catalysts can be also obtained by one-pot preparation method, only solving small quantities of metallic salts in the lignin solution. In addition, alumina and silica-coated lignin fibers were produced by feeding a partially gelated solution of the respective alkoxide through the outer needle of the spinneret. The coated fibers can be carbonized without thermostabilization step, decreasing considerably the preparation time. All these carbon materials were successfully tested in different applications such as heterogeneous catalysis, energy storage and environmental protection, confirming that electrospinning is a powerful tool for maximizing the value of lignin as carbon precursor.